"Holding your breath": Interviews with young people who have undergone predictive genetic testing for huntington disease - Duncan, R; Gillam, L; Savulescu, J; Williamson, R; Rogers, J; Delatycki, M (2007)
Guidelines recommend that predictive genetic testing for Huntington disease (HD) should be deferred until the age of majority (18 years in most countries). However, opposition to these guidelines exists, with some professionals arguing that testing may be beneficial for young people, and should be considered much earlier. Empirical evidence is unable to substantiate either position. We aimed to (1) explore the experience of predictive genetic testing for HD from the young person's perspective and to (2) document the impact that testing has upon various aspects of young people's lives. Eight young people who had undergone predictive genetic testing for HD were interviewed. They ranged in age from 17 to 25 years at the time of their test. Four were female and two had received a gene-positive test result. Interviews were taped, transcribed and analyzed thematically. Three themes emerged related to the time before the test was performed: "Living as though gene-positive," "Risk behaviors," and "Complex pasts." Two themes emerged related to the time after testing: "Identity difficulties" and "Living again." When the young people spoke about their experiences of predictive testing, they placed these within a broader context of growing up in a family affected by HD. For some of the young people, uncertainty about their genetic status constituted a barrier in their lives and prevented them from moving forward. Testing alleviated these barriers in some cases and helped them to move forward and make significant behavioral changes. Not one of the young people intetviewed regretted undergoing predictive testing. © 2007 Wiley-Liss, Inc.